Hidroquímica do aquífero pré-cambriano no estado de São Paulo - Roque, Diogo Alberto [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The crystalline basement of the São Paulo State consists of Pre-Cambrian igneous and metamorphic rocks, composing the Pre-Cambrian Aquifer System (SAC). Aquifer rocks are susceptible to alteration processes involving different chemical reactions. Seeking to understand if there are relations between the water chemistry of the SAC and its lithotypes, this work analyzed hydrochemical data from the CETESB Groundwater Quality Report, triennium 2013-2015. 343 water samples were collected at 65 points in the study area. Analyzed samples were selected from the calculation of ionic balance, assuming an error between ± 15%. One sample per well was selected. Univariate and multivariate statistical treatment was performed, as Piper and Stiff diagrams for hydrochemical classification and visualization of spatial distribution of hydrochemical facies. Water-rock interaction models were proposed from chemical reactions of minerals with groundwater. Major anion in water is bicarbonate (HCO3 -) and major cátions are calcium (Ca2+) and sodium (Na+). Some samples show high concentrations of chloride (Cl-) and sulphate (SO4 2-) ions, which may indicate contamination of anthropogenic origin. PH values range from 5,00 to 9,03, averaging 6,97. Electrical conductivity values range from 18 μS/cm to 387,00 μS/cm, averaging 181,22 μS/cm. It was concluded that in Pre-Cambrian Aquifer System predominates calcium bicarbonate waters and, subordinately, sodium bicarbonate waters

O embasamento cristalino do estado de São Paulo consiste em rochas ígneas e metamórficas de idade Pré-Cambriana que compõem o Sistema Aquífero Pré- Cambriano (SAC). As rochas de um aquífero são altamente suscetíveis a processos de alteração envolvendo diferentes tipos de reações químicas. Buscando entender se há relações entre o quimismo das águas do SAC e seus litotipos, este trabalho analisou dados hidroquímicos provenientes do Relatório de Qualidade das Águas Subterrâneas da CETESB, triênio 2013-2015. Foram utilizados dados de 343 amostras de água coletadas em 65 pontos na área de estudo. As amostras analisadas foram selecionadas a partir do cálculo de balanço iônico, admitindo-se erro compreendido entre ± 15%. Selecionou-se uma amostra por poço. Foi realizado tratamento estatístico univariado e multivariado e confeccionados diagramas de Piper e Stiff para classificação hidroquímica das águas e visualização da distribuição espacial das fácies hidroquímicas. Foram propostos modelos de interação águarocha a partir das reações químicas dos minerais com a água subterrânea. O principal ânion presente nas águas é o bicarbonato (HCO3 -) e os principais cátions o cálcio (Ca2+) e o sódio (Na+). Algumas amostras apresentam altas concentrações dos íons cloreto (Cl-) e sulfato (SO4 2-), podendo indicar contaminação de origem antrópica. Os valores de pH para a área variam entre 5,00 a 9,03, com média 6,97. A condutividade elétrica varia entre 18 μS/cm e 387,00 μS/cm, com média 181,22 μS/cm. Concluiu-se que predominam no Sistema Aquífero Pré-Cambriano águas bicarbonatadas cálcicas e, subordinadamente, bicarbonatadas sódicas
Keywords: Química da água; Aquiferos; Rochas igneas; Rochas metamorficas; Águas subterrâneas - Qualidade - 2013-2015; Hidrogeologia; São Paulo (Estado)